Greenhouse gas emissions avoidance by photovoltaic plants on the road to carbon neutrality - Távora, J.; Cortinhal, M. J.; Meireles, M. (The European Photovoltaic Solar Energy Conference and Exhibition (EU PVSEC 2021), 2021)
Roadmaps to carbon neutrality challenge GHG emissions savings by solar PV energy: current systems are still largely produced using fossil fuels and PV plants occupy for decades land areas that might capture and store atmospheric carbon. We take primary emissions from three PV technologies and secondary emissions from vegetation clearing in PV power plant sites and compare them to lifecycle emissions savings from PV energy over continental Portugal assuming that the carbon intensity of the electrical grid is decreased linearly to near zero in thirty years. The balance is revealed by the emissions payback time (CPBT) metric. In our approach, time affects emissions over a PV plant’s lifetime in three ways: overall decreasing grid carbon intensity, yearly avoided grid emissions, and yearly cancelled carbon capture due to land cover clearing - a forest of planted eucalyptus trees. Results for mono-Si reveal mean emissions payback times of 14 years for the lowest irradiation places, and 10.5 to 12.5 years for 93% of the territory. Secondary emissions increase the mean value to 19, with a maximum of 24 years. These figures strongly recommend that national regulators enforce checks on primary and secondary emissions by PV systems sited on forested land.